Strategic information systems planning in Malaysian public universities - Ismail, Noor Azizi; Raja Mohd Ali, Raja Haslinda; Mat Saat, Rafeah; Mohamad Hsbollah, Hafizah (Emerald Group Publishing Limited, 2007)
Purpose– The paper's purpose is to investigate the current status, problems and benefits of strategic information systems planning implementation in Malaysian public universities.Design/methodology/approach– The study uses dual but mutually supportive strands of investigation, i.e. a questionnaire survey and interviews.Findings– Malaysian public universities are aware of the importance of SISP. While only one university has implemented SISP, 15 others are either at the implementation or planning stage. These universities are suggested to devote more time, efforts, and resources to successfully implement the SISP initiative.Originality/value – This is the first study to investigate SISP status and process in Malaysian public universities using a combination of quantitative and qualitative data.